DESCRIPTION OF THE STAGES OF PREPARING STUDENTS FOR PRACTICAL ACTIVITIES IN ELECTRICAL ENGINEERING - Norkulov Usman Elomonovich (American Journals, 2025)
In organizing electrical engineering education, it is important to clarify its goals and objectives, content, form, methods and means of education. If we divide the entire period of professional training in higher education institutions into three stages, then the motivational components of training are presented. This article examines the special aspects of the organization of students' practical training in the field of the concept of a conceptual model, which is a basic psychological concept that reveals various aspects of mental reflection in electrical engineering activities.
Keywords: Education, pedagogical, information, technological, engineering, technology, psychology, model.